SISTEM SOSIAL-BUDAYA DI INDONESIA - Kistanto, Nurdien H. (Sabda: Jurnal Kajian Kebudayaan, 2008)
Human creature and culture together build a socio-cultural life, patterned and systematically referred to a socio-cultural system. Systematization through adjustments with the socio-cultural thoughts and practices in norms, ideas, values, aesthetics, tradition, all of which can be realized through cultural elements, at one time was the cultural content. Socio-cultural systems can be understood as the bowl of developing cultural elements as the embodiment of cultural contents which are intertwined. Five Indonesian socio-cultural systems, which are formed by cultural background and experiences from period to period, can be considered as the fruits of civilization and nation experiences perpetually moving and growing.